High normal blood pressure and hypertension among Polish students: prevalence and risk factors - Szafraniec, Dominika; Czarny, Wojciech (Anthropological Review, 2019)
The purpose of this work was twofold: to determine prevalence of hypertension and high normal blood pressure in university students, and to assess impact of body weight status, field of study and selected lifestyle factors on the arterial blood pressure (BP) values. The research was conducted in a group of 731 male and female full-time academic students who volunteered as participants in the study. The thickness of skinfolds was measured in three standard places. The percentage of fat was determined using the body composition analyzer. Body height and mass, waist circumference, hips and the largest right thigh circumference were measured and anthropometric indices calculated. The blood pressure values were measured according to the Korotkov method. Data were analyzed using quantitative and qualitative methods, oneway analysis of variance (ANOVA) and linear regression analysis. The chi-square test of independence and linear regression analysis were used to assess impact of selected factors on BP values. High normal BP was found in 19% of women and 23% of men, and hypertension in 10% of women and 32% of men. Factors having a very high effect on BP values in both women and men were the somatic structure and fat content in the body. A positive correlation was found between subscapularis muscle fatty infiltration and BP values in both women and men. Majority of lifestyle factors were not associated with BP values but smoking and alcohol consumption. The field of study and level of physical activity were directly associated with high normal BP and hypertension. In conclusion it should be stated that high blood pressure is a growing problem in young adult people with men being more likely to be exposed to this condition than women.